Prospective study evaluating the incidence of bacteraemia and bacteruria in afebrile and febrile neutropaenic dogs undergoing chemotherapy. Issue 4 (14th November 2016) - Shaffer, Kimberly; Bach, Jonathan; Chun, Ruthanne
Abstract: The purpose of this prospective study was to determine the incidence and character of bacteraemia and bacteruria in afebrile and febrile neutropaenic dogs undergoing cytotoxic chemotherapy. Fifty‐five neutropaenic dogs presenting to the University of Wisconsin Veterinary Medical Teaching Hospital were enrolled for a total of 57 neutropaenic episodes. The overall incidence of bacteraemia was 12.3% ( n  = 7/57). Three afebrile dogs and four febrile dogs were bacteraemic; this difference was not significant ( P  = 0.6968). The overall incidence of bacteruria was 7.5% ( n  = 4/53). Two afebrile dogs and two febrile dogs were bacteruric; this difference was not significant ( P  = 1.0). Of the positive blood cultures, the majority of organisms cultured ( n  = 6/7) were gram‐positive organisms with one gram‐negative organism. Three of the positive blood cultures showed in vitro resistance to more than one antimicrobial agent. Clinical parameters (age, body weight, heart rate, rectal temperature, neutrophil count, haematocrit and platelet count) were not predictive of bacteraemia. The results of this study were not sufficient to justify the use of blood cultures as a first‐line diagnostic test for neutropaenic patients. Blood cultures may have utility in individual case management for a minority of patients in guiding antibiotic choice in the case of resistant bacterial infections. Blood cultures may serve as a tool for antimicrobial de‐escalation, although further study is needed. Abstract : The incidence of bacteraemia in 55 neutropaenic dogs undergoing chemotherapy was found to be 12.3%. The incidence in febrile and afebrile groups was not significantly different. Of positive blood cultures, 42.9% were multi‐drug–resistant organisms highlighting the value of blood cultures in this patient population.